COMPILATION OF HERPETOFAUNA CATALOGUE OF THE NGLAGGERAN ANCIENT VOLCANO AREA AS AN ALTERNATIVE LEARNING MEDIA FOR BIODIVERSITY MATERIALS FOR GRADE X SMA/MA - Sulistio, Adian Dwi; Putri, Rizka Apriani (Jurnal Edukasi Biologi, 2025)
This research aims to (1) determine the feasibility of the herpetofauna catalogue media based on the assessment of material experts and media experts and (2) determine the feasibility of the herpetofauna catalogue media based on the assessment of learning practitioner experts and students. This research employs the Research and Development (RD) method, utilising the ADDIE model, which is limited to the ADD (Analysis, Design, Development) stage. This research was conducted at the Faculty of Mathematics and Natural Sciences, UNY, with the subjects of this research comprising a material expert, a media expert, a biology teacher in grade X, and 26 students. Data collection was conducted using assessment instruments tailored for media experts, material experts, biology teachers of grade X high schools, and students. These instruments were compiled based on the assessment instruments outlined in high school textbooks, as per the BSNP (National Education Standards Agency) guidelines, and relevant research instruments. Data analysis was carried out descriptively and qualitatively. The results of this research are the Herpetofauna Catalogue of the Nglanggeran Ancient Volcano Area, serving as an alternative learning medium for Grade X high school students on biodiversity material. The developed catalogue has met the feasibility criteria assessed by material experts, media experts, learning practitioner experts, and students. This research is important in providing teachers with alternative learning media that capitalise on local potential. Further research is needed on the effectiveness of the media and the development of a catalogue for a wider range of materials.